Bahasa inggris - Herlina Rufitriansyah; Siswana (UIN Alauddin Makassar, 2024)
This study aims to analyse the type of code-mixing that occurs by English teachers when teaching English lessons, and find out the reasons for the use of code-mixing. This research uses descriptive qualitative research. The object of this research is one English teacher in Private Vocational School in Bogor. The process of collecting the data, the researcher recorded the teacher's voice audio when teaching in class and also when conducting interviews. The data analysis technique used Muysken's theory. In this study, it was found that there were three types of code mix used by the teacher when teaching, namely the type of insertion, alternation, and lexical congruence. The use of insertion type is about 55%, then alternation 44%, and lexical congruent 1%, from 158 total utterances obtained. The results found in this study are that teachers more often use code-mixing insertion type when teaching English. Then three reasons for the use of code-mixing by the teacher, namely because of the background of a major school, for students' understanding of the material, and the existence of limited student understanding in English.